Regional guidelines for identifying genetic conservation units and seed sources - Bioversity International And International Center For Tropical Agriculture; Asia Pacific Forest Genetic Resources Programme (2025)
The objectives of this guideline are to: • enable a regional assessment of the conservation status of native Asian tree species and their genetic resources using readily available information • enable the identification and recognition of sites that already serve, or have the potential to serve, as genetic conservation units and seed sources for native tree species, so that relevant measures can be taken to safeguard them • support the identification of priorities and collaboration opportunities for ecological and genetic research on native Asian tree species across country borders • raise forest managers’ and conservation practitioners’ awareness about the importance of conserving genetic diversity, by highlighting related gaps and priorities that may differ from gaps and priorities identified solely at species or ecosystem level.